From Protein Structures to Functional Biomimetics - Durukan, Canan; Grossmann, Tom N. (Synlett, 2024)
The development of complex molecular scaffolds with defined folding properties represents a central challenge in chemical research. Proteins are natural scaffolds defined by a hierarchy of structural complexity and have evolved to manifest unique functional characteristics; for example, molecular recognition capabilities that facilitate the binding of target molecules with high affinity and selectivity. Utilizing these features, proteins have been used as a starting point for the design of synthetic foldamers and enhanced biocatalysts, as well as bioactive reagents in drug discovery. In this account, we describe the strategies used in our group to stabilize protein folds, ranging from the constraint of bioactive peptide conformations to chemical protein engineering. We discuss the evolution of peptides into peptidomimetics to inhibit protein–protein and protein–nucleic acid interactions, and the selective chemical modification of proteins to enhance their properties for biotechnological applications. The reported peptide- and proteomimetic structures cover a broad range of molecular sizes and they highlight the importance of structure stabilization for the design of functional biomimetics.1 Introduction2 Constraining the Conformation of Peptides3 Peptide-Based Covalent Protein Modifiers4 Chemical Protein Engineering5 Conclusions
Keywords: INCYPRO; peptidomimetics; protein engineering; protein–protein interactions; proteomimetics; structure-based design